Gains in Maize Genetic Improvement in Eastern and Southern Africa: II. CIMMYT Open‐Pollinated Variety Breeding Pipeline. Issue 1 (8th December 2016) - Masuka, Benhilda; Magorokosho, Cosmos; Olsen, Mike; Atlin, Gary N.; Bänziger, Marianne; Pixley, Kevin V.; Vivek, Bindiganavile S.; Labuschagne, Maryke; Matemba‐Mutasa, Rumbidzai; Burgueño, Juan; Macrobert, John; Prasanna, B. M.; et al.
Abstract : Open‐pollinated varieties (OPVs) still represent a significant proportion of the maize ( Zea mays L.) seed system in many countries of sub‐Saharan Africa. The International Maize and Wheat Improvement Centre (CIMMYT) has been breeding improved maize varieties for the stress‐prone environments experienced by most smallholder farmers in eastern and southern Africa for over 30 yr. Hybrid breeding is now the major focus of the CIMMYT breeding pipeline. However, OPVs are generated within the hybrid pipeline. This is the first study to document genetic gain for maize grain yield under both optimal and stress (random and managed drought, low nitrogen [N], and maize streak virus [MSV]) conditions within the CIMMYT eastern and southern African OPV breeding pipeline. Genetic gain was estimated using the slope of the regression on the year of OPV release in regional trials over a 12‐yr period (1999–2011). Open‐pollinated varieties were separated into two maturity groups, early (<70 d to anthesis) and intermediate‐late (>70 d to anthesis). Genetic gain in the early maturity group under optimal conditions, random drought, low N, and MSV was 109.9, 29.2, 84.8, and 192.9 kg ha −1 yr −1 . In the intermediate‐late maturity group, genetic gain under optimal conditions, random drought, low N, and MSV was 79.1, 42.3, 53.0 and 108.7 kg ha −1 yr −1 . No significant yield gains were made under managed drought stress for both maturity groups. Our results show continued improvement in OPVs for both yield potential and stress tolerance.